2013
DOI: 10.4236/ss.2013.43036
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Postoperative Bleeding after Neck Surgery

Abstract: Objective: To review the characteristics of and the procedure for preventing postoperative bleeding after neck surgery. Materials and Methods: A retrospective review of 9 patients (9/893; 1.0%) with postoperative bleeding who required reoperation was performed to analyze clinical findings. Results: There was no significant difference in the incidence of bleeding between types of surgical procedures. Postoperative bleeding occurred within 24 hours in all cases except 2, in which it occurred 7 days or more after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Postoperative bleeding should always be considered surgically related until proven otherwise [20]. The incidence of postoperative bleeding in this study was 7.8% which is higher than in other studies which reported the incidence of less than 2% [21] [22]. There was no significant difference in occurrence of bleeding as far as age, gender and underlying medical condition were concerned.…”
Section: Discussioncontrasting
confidence: 63%
“…Postoperative bleeding should always be considered surgically related until proven otherwise [20]. The incidence of postoperative bleeding in this study was 7.8% which is higher than in other studies which reported the incidence of less than 2% [21] [22]. There was no significant difference in occurrence of bleeding as far as age, gender and underlying medical condition were concerned.…”
Section: Discussioncontrasting
confidence: 63%
“…Several studies have reported on the site of hemorrhage, but most have not reported distinct bleeding points during the wound exploration. Nambu concluded that the hemorrhage site during postoperative neck surgery mostly occurred on the muscle surface, and excessive muscle subtraction and too much blunt dissection may be the causes of bleeding [18]. The feeding vessels of the vertebral body are often found on the ventral side of the longus colli.…”
Section: Discussionmentioning
confidence: 99%
“…6 The majority of hemorrhages present within the first 24 hours of surgery. 6,15 Monitoring for postoperative hypocalcemia involves observing for symptoms (perioral/extremities paresthesia and numbness) and signs of hypocalcemia (Chvostek's and Trousseau signs) and serial monitoring of serum/ionized calcium. In some patients, there may be a delayed fall in serum calcium (5-7 days) following surgery.…”
Section: The Roc Curvementioning
confidence: 99%